MARKET MICROSTRUCTURE IN PRACTICE. - Lehalle, Charles-Albert (WSPC, 2013)
Market Microstructure in Practice comments on the consequences of Reg NMS and MiFID on market microstructure. It covers changes in market design, electronic trading, and investor and trader behaviors. The emergence of high frequency trading and critical events like the ""Flash Crash"" of 2010 are also analyzed in depth. Edited by Charles-Albert Lehalle and Sophie Laruelle, and with contributions from Romain Burgot, Stéphanie Pelin and Matthieu Lasnier, this book uses a quantitative viewpoint to help students, academics, regulators, policy makers, and practitioners understand how an attrition o.